ANALISIS MEDAN MAKNA ‘SENI BELA DIRI KHAS JEPANG’ DALAM HURUF KANJI BU (武) - Irwan Irwan; Mulyadi Mulyadi (IZUMI, 2017)
(Title: Meaning Field Analysis Of 'Japan's Martial Arts' In Kanji’s Letter Of Bu (武) )This research analyze the kind of words exist in the semantic field of the lexem of kanji BU (武) in Japanese, and how the lexical relation and the semantic feature were formed on each word that exist in one of semantic field. The lexem of kanji BU (武) is literally translated as martial arts, which is general meaning and also has derivatives meaning (hyponim), it creates the semantic field. The type of the research is qualitative research using inter lingual match method. The basic technique method used in this research is the technique of determining element (PUP technique) which  applying equal compare connect technique (HBS) and the difference compare connect technique (HBB). The data taken from the book "BUDO: The Martial Ways of Japan" as the primary data, and various articles from scientific journals that discuss the semantic field as supporting data. As the result of the research, found 2 lexems which play role as sub-semantic field of the kanji BU, they are BUJUTSU (武術) and BUDO (武道). Out of the two sub-semantic fields, found 10 words that became hyponim of BUJUTSU and 9 words that became hyponim of BUDO.   gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor